2021
DOI: 10.1111/jgh.15382
|View full text |Cite
|
Sign up to set email alerts
|

Calcarine as a bridge between brain function and structure in irritable bowel syndrome: A multiplex network analysis

Abstract: Background and Aim Jointly analyzing structural and functional brain networks enables a better understanding of pathological underpinnings of irritable bowel syndrome (IBS). Multiplex network analysis provides a novel framework to study complex networks consisting of different types of connectivity patterns in multimodal data. Methods In the present work, we integrated functional and structural networks to a multiplex network. Then, the multiplex metrics and the inner‐layer/inter‐layer hub nodes were investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…The calcarine sulcus was located posterior to the medial surface of the hemisphere. Less activation of the bilateral anterior calcarine sulcus was associated with better delayed recall in amnestic MCI patients ( Chen et al, 2021 ; Lejko et al, 2022 ).…”
Section: Discussionmentioning
confidence: 93%
“…The calcarine sulcus was located posterior to the medial surface of the hemisphere. Less activation of the bilateral anterior calcarine sulcus was associated with better delayed recall in amnestic MCI patients ( Chen et al, 2021 ; Lejko et al, 2022 ).…”
Section: Discussionmentioning
confidence: 93%
“…In recent years, research has been conducted to model and analyze the interdependent brain connectome that comprises SC and FC layers. For instance, several studies have employed integrated SC and FC features in the multilayer connectome to reveal nontrivial properties, such as overabundant network motifs or subgraphs [13][14][15][16] , core hub regions [17][18][19] , and core-periphery structures 20,21 . However, whether and how the SC and FC layers show different connectivity profiles in the interacting connectome are not yet well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Previous neuroimaging studies have reported structural and functional brain abnormalities in IBS patients compared to healthy controls (HCs) [3]. Resting-state functional magnetic resonance imaging (rs-fMRI) is an advanced and non-invasive technique used to measure brain activity, which does not require participants to engage in specific tasks.…”
Section: Introductionmentioning
confidence: 99%